La interconexión entre Castilla, Galicia y Portugal en la confección de las crónicas medievales y en la transmisión de textos literarios - Ramón, LORENZO (Revista de Filología Románica, 2002)
There is a wide interconnexion in the process of composition and transmission of texts between Castile, Galicia and Portugal in the Middle Ages. In this essay I analyse some cases of this close relationship between Castile and the western part of the Iberian Peninsula, and present a range of examples of the complex construction and evolution of quite a good number of texts, both historical (Chronicle of Alfonse X, Chronicle of Castile, Galician translation, Chronicle of 1344 —Portuguese and Spanish—, Chronicle of 1404, Chronicle of the Moor Rasis) and literary (Trojan Chronicle, The Holy Grail, Merlin, The Book of Tristram). I compare the different texts and try to emphasize the essential importance of many cases of the texts elaborated in the West of the Iberian Peninsula.